Moving beyond the MLA & deviant modes of scholarly communication - Askey, Dale (My University, 2006)
This talk, presented by a librarian for an audience of researchers in the humanities, consists of two distinct parts. The first half addresses the deficiencies of the MLA International Bibliography and points out alternatives that provide better coverage of the disciplinary literature. Also presented are strategies and ideas for doing better research with the tools at hand, such as Google Scholar. The second half of the talk makes a case for converting existing journals to an open access model. Additionally, methods for making open access journals more easily located and cited are covered.
Keywords: MLA; Scholarly communication; Literature; Open access publishing